Islam Explained - Kadir, Shaik (Marshall Cavendish International, 2017)
Islam, a faith that embraces all races and cultures, has spread far and wide across the globe, and today about one in five people in the world is a follower of the Islamic faith. Few people have not heard about Islam or interacted with Muslims. But many, including some Muslims, do not know much about Prophet Muhammad or what the Qur'an actually teaches. Unfortunately, the focus on terrorism may have resulted in an inaccurate and biased view of Islam and of Muslims in general. Islam is not responsible for those Muslims involved in terrorism and violence; these Muslims make up only a tiny fracti